Discursos e efeitos: problematizando a temática das altas habilidades/superdotação sob as tramas da inclusão educacional - Speroni, Karine Sefrin (2012)
This study aimed to investigate and discuss "High Abilities/Giftedness (HA/G) Theme" under Educational Inclusion aspects (EI), as well as its accessibility. To this end, other dialogues possibilities with these themes were attempted to carry out undertaking approaches to some tools found in Michel Foucault's studies. The production process of subject "with high ability/giftedness characteristics" was the primary input developed by the Research Group on Special Education - Social Inclusion (RGSE) in 2009 at some Municipal school in Santa Maria City/Rio Grande do Sul State. One focus group was used with four members of RGSE that developed the research in such school, in order to rescue the official discourse of the mentioned group focusing the school context. Furthermore, four narrative interviews types were used with five issues driving the dialogue with teachers of Early School Years who indicated students in the survey performed by RGSE in 2009, with school managers, with the teachers of Special Education, and with the teachers of these students today. With this research, it was possible to consider other perspectives on the production of subjects with "HA/G" facing the context of educational inclusion, particularly to discuss some established truths about this theme that is understood by Special Education. Moreover, it can be noted that the RGSE speech articulates a wide range of truths regimes in that School context. It can be seen through the found discursive networks that HA/G speeches about verbal exchanges of Educational Inclusion permeate antagonism, i.e., subjects who have "high ability/giftedness characteristics " are "visible" in the context of Early School Years and "invisible" in the context of school management and teachers of Final Years of elementary education. Therefore, HA/G theme on Special Education may constitute a subjected know and subjecting the schooling contexts with particular cultures, so there is resistance that enables the inclusion/exclusion of subject. In that context, accessibility is discursively stated under architectural prism and face to HA/G may permeate the invisibility principle.